The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/efp.12041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ceratocystis wilt on eucalyptus tree growth and cellulose pulp yield

Abstract: In this study, we determined the effects of Ceratocystis fimbriata wilt on volumetric growth and cellulose pulp yield of eucalyptus. Sevenyear-old healthy and infected trees were separated into different classes of severity, and the individual volume of each whole tree with bark was determined. Volumetric losses were found regardless of the class of disease severity, resulting in reduction in volumetric growth of the trees from 65% to 87%, depending on the infection level. Two approaches were used for evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 18 publications
1
26
1
3
Order By: Relevance
“…Mafia et al. () observed that eucalypt trees infected by C. fimbriata required a greater alkaline load (23.8%) during cooking and yielded less pulp (13.7%). The authors also reported that volumetric growth in infected trees decreased by 65%–87%, depending on disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Mafia et al. () observed that eucalypt trees infected by C. fimbriata required a greater alkaline load (23.8%) during cooking and yielded less pulp (13.7%). The authors also reported that volumetric growth in infected trees decreased by 65%–87%, depending on disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the death of plants and reduction of volumetric growth in the field, diseased trees have lower cellulose yield, and their wood has lower commercial value for timber (Alfenas and Ferreira ; Mafia et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ceratocystis wilt, which is caused by Ceratocystis fimbriata Ellis & Halsted, is currently one of the most important diseases in eucalypt. This pathogen has a wide geographic distribution and a broad host range and results in significant yield losses (Alfenas et al 2009;Fernandes et al 2014;Mafia et al 2013). This disease can reduce the volumetric growth of trees in the field by up to 87%, the cellulose yield by approximately 14%, and the value of wood for sawing (Mafia et al 2013).…”
Section: Introductionmentioning
confidence: 99%